Promyelocytic leukemia protein targets MK2 to promote cytotoxicity. (11th October 2021) - Chen, I‐Ting; Chen, Hsiao‐Chi; Lo, Yu‐Hsun; Lai, Peng‐Yeh; Hsieh, Fu‐Yi; Wu, Yung‐Hsuan; Shih, Hsiu‐Ming; Lai, Ming‐Zong
Abstract: Promyelocytic leukemia protein (PML) is a tumor suppressor possessing multiple modes of action, including induction of apoptosis. We unexpectedly find that PML promotes necroptosis in addition to apoptosis, with Pml −/− macrophages being more resistant to TNF‐mediated necroptosis than wild‐type counterparts and PML‐deficient mice displaying resistance to TNF‐induced systemic inflammatory response syndrome. Reduced necroptosis in PML‐deficient cells is associated with attenuated receptor‐interacting protein kinase 1 (RIPK1) activation, as revealed by reduced RIPK1[S166] phosphorylation, and attenuated RIPK1‐RIPK3‐MLKL necrosome complex formation. We show that PML deficiency leads to enhanced TNF‐induced MAPK‐activated kinase 2 (MK2) activation and elevated RIPK1[S321] phosphorylation, which suppresses necrosome formation. MK2 inhibitor treatment or MK2 knockout abrogates resistance to cell death induction in PML‐null cells and mice. PML binds MK2 and p38 MAPK, thereby inhibiting p38‐MK2 interaction and MK2 activation. Moreover, PML participates in autocrine production of TNF induced by cellular inhibitors of apoptosis 1 (cIAP1)/cIAP2 degradation, since PML‐knockout attenuates autocrine TNF. Thus, by targeting MK2 activation and autocrine TNF, PML promotes necroptosis and apoptosis, representing a novel tumor‐suppressive activity for PML. SYNOPSIS: Promyelocytic leukemia protein promotes TNF‐induced necroptosis via two distinct pathways, firstly by inhibiting MAPK activated kinase 2 activation, and secondly by enhancing autocrine TNF generation. Promyelocytic leukemia protein (PML) promotes necroptosis. PML targets MAPK activated kinase 2 (MK2) and inhibits MK2 activation to enhance necroptosis. PML also increases autocrine production of tumor necrosis factor (TNF) and associated necroptosis induction. Abstract : Promyelocytic leukemia protein promotes TNF‐induced necroptosis via two distinct pathways, firstly by inhibiting MAPK activated kinase 2 activation, and secondly by enhancing autocrine TNF generation.